Comparison of Product Quality, Promotion Strategy, Physical Evidence of Holland Bakery and Vanhollano Bakery in Millennial and Generation Z in The City Of Pekanbaru - Laurencia, Cristine; Berampu, Lailan Tawila; Wildah, Sri Wahyuni; Noviasari, Henni (Economics, Business and Management Science Journal, 2026)
This study aims to find out the comparison of product quality, promotional strategies, and physical evidence  of Holland Bakery and Vanhollano Bakery in the Millennial Generation and Generation Z in the city of Pekanbaru. This study uses a qualitative approach with a survey method to collect data. The population needed is the Millennial Generation and Generation Z in the city of Pekanbaru who have bought and consumed products from Holland Bakery and Vanhollano Bakery. Data analysis was carried out by descriptive analysis and hypothesis testing using the paired sample t-test method and SPSS software version 22 to find out if there is a difference between the two objects studied. The results of this study show that there is a significant difference between Millennials and Generation Z regarding the promotional strategies of Holland Bakery and Vanhollano Bakery. However, in the variables of product quality and physical evidence, no difference was found between the two brands compared to the two generations. This shows that the rpomosi strategy is one of the distinguishing factors in assessing Holland Bakery and Vanhollano Bakery among the two generations